Failure of podocalyxin suppression and HOXA10/HOXA11 activation characterizes endometrial dysfunction in hyperandrogenic PCOS - Celik, Nilufer; Celik, Onder; Ulug, Ulun; Ersahin, Aynur; Gurkan, Naziye; Gungor, Kagan; Duran, Cevdet (Elsevier Ireland Ltd, 2026)
To analyze the effects of hyperandrogenemia (HA) in polycystic ovary syndrome (PCOS) on negative and positive regulators of endometrial receptivity. Fifty-four women with PCOS undergoing total embryo freezing were classified into four phenotypes: classical type A, classical type B, ovulatory type C, and normoandrogenic type D. Hyperandrogenemia was present in phenotypes A-C and absent in phenotype D. Twenty-five age-matched infertile women without clinical or biochemical features of PCOS served as controls. Endometrial sampling was performed on day five after oocyte retrieval. Relative PCX mRNA and protein levels, together with HOXA10 and HOXA11 mRNA expression, were evaluated. Immunohistochemical analysis was performed to assess the spatial distribution of PCX, and H-score values were compared between the PCOS and control groups. PCX mRNA expression and protein concentration were significantly higher in the PCOS group compared with controls (all p < 0.001), consistent with the significantly higher H-score values observed in the PCOS group (p < 0.001). In contrast, HOXA10 and HOXA11 mRNA expression levels were significantly reduced in PCOS patients (all p < 0.001). Among PCOS phenotypes, those associated with hyperandrogenemia exhibited significantly lower HOXA10 and HOXA11 expression than the normoandrogenic phenotype (all p < 0.005). PCX mRNA and protein levels were significantly higher in classical and ovulatory hyperandrogenic phenotypes compared with the normoandrogenic group (all p < 0.005). PCX was identified as a negative predictor of HOXA10 and HOXA11 expression, while testosterone negatively predicted HOXA10 and HOXA11. Insulin resistance and testosterone were positive predictors of PCX expression, whereas progesterone levels on the day of oocyte retrieval and on day five after retrieval were negative predictors of PCX expression. Hyperandrogenemia disrupts the physiological mid-luteal downregulation of PCX and the upregulation of HOXA10 and HOXA11, leading to impaired endometrial receptivity and displacement of the implantation window in PCOS.
Keywords: Polycystic ovary syndrome; Hiperandrogenemia; Receptivity; Podocalyxin; HOXA; Implantation window